MiR-193b inhibits autophagy and apoptosis by targeting IGFBP5 in high glucose-induced trophoblasts. (November 2020) - Ji, Yanting; Zhang, Wenfeng; Yang, Jin; Li, Changzhong
Abstract: Introduction: Inhibiting apoptosis of trophoblasts in women with gestational diabetes mellitus (GDM) is expected to guarantee adequate nutrition for the fetus and avoid abortion. MiR-193b is one of the most downregulated miRNAs in GDM patients. However, less is known about the role of miR-193b in autophagy and apoptosis in GDM patients. Methods: We detected the expression of miR-193b in GDM patients. Then, we cultured human trophoblasts (HTR8 cells) with high glucose (HG) to simulate a diabetic environment in vitro, and further explored the effects of miR-193b on apoptosis and autophagy of HG-treated HTR8 cells. Results: The expression of miR-193b was significantly downregulated in the peripheral blood of GDM patients compared with healthy controls, and decreased miR-193b caused apparent autophagy and a substantially high apoptosis rate in HG-treated HTR8 cells. These effects were reversed by enhancing miR-193b expression or using the autophagy inhibitor 3-MA. Inhibiting miR-193b induced the pro-autophagic, cytostatic, and pro-apoptotic effects reduced by 3-MA in HTR8 cells upon HG treatment. Moreover, the expression of insulin-like growth factor-binding protein 5 (IGFBP5) was upregulated notably in the peripheral blood of GDM patients, and IGFBP5 appears to represent a direct miR-193b target. Note that silencing IGFBP5 blocked autophagy and apoptosis in HG-treated HTR8 cells, an effect that was diminished by inhibiting miR-193b. Conclusion: Our data indicate that aberrantly low expression of miR-193b in HG-induced trophoblasts results in massive apoptosis events by upregulating IGFBP5-induced autophagy, which may trigger GDM. Therefore, miR-193b may became a potential target for GDM therapy. Highlights: Downregulation of miR-193b appears in GDM patients. MiR-193b suppresses apoptosis and autophagy in HG induced trophoblasts. IGFBP5 is a direct miR-193b target in trophoblasts. Inhibiting miR-193b reverses the alleviation effect of si-IGFBP5 on HG-induced autophagy.